Assessing Sex, Gender Identity, Sexual Orientation, Race, Ethnicity, Socioeconomic Status, and Mental Health Concerns in Tobacco Use Disorder Treatment Research: Measurement Challenges and Recommendations From a Society for Research on Nicotine and Tobacco Pre-conference Workshop. Issue 5 (8th October 2021) - Weinberger, Andrea H; Steinberg, Marc L; Mills, Sarah D; Dermody, Sarah S; Heffner, Jaimee L; Kong, Amanda Y; Pang, Raina D; Rosen, Rachel L
Abstract: This paper reports on topics discussed at a Society for Research on Nicotine and Tobacco pre-conference workshop at the 2019 annual Society for Research on Nicotine and Tobacco meeting. The goal of the pre-conference workshop was to help develop a shared understanding of the importance of several tobacco-related priority groups in tobacco use disorder (TUD) treatment research and to highlight challenges in measurement related to these groups. The workshop focused on persons with minoritized sex, gender identity, and sexual orientation identities; persons with minoritized racial and ethnic backgrounds; persons with lower socioeconomic status (SES); and persons with mental health concerns. In addition to experiencing commercial tobacco-related health disparities, these groups are also underrepresented in tobacco research, including TUD treatment studies. Importantly, there is wide variation in how and whether researchers are identifying variation within these priority groups. Best practices for measuring and reporting sex, gender identity, sexual orientation, race, ethnicity, SES, and mental health concerns in TUD treatment research are needed. This paper provides information about measurement challenges when including these groups in TUD treatment research and specific recommendations about how to measure these groups and assess potential disparities in outcomes. The goal of this paper is to encourage TUD treatment researchers to use measurement best practices in these priority groups in an effort to conduct meaningful and equity-promoting research. Increasing the inclusion and visibility of these groups in TUD treatment research will help to move the field forward in decreasing tobacco-related health disparities. Implications: Tobacco-related disparities exist for a number of priority groups including, among others, women, individuals with minoritized sexual and gender identities, individuals with minoritized racial and ethnic backgrounds, individuals with lower SES, and individuals with mental health concerns. Research on TUD treatments for many of these subgroups is lacking. Accurate assessment and consideration of these subgroups will provide needed information about efficacious and effective TUD treatments, about potential mediators and moderators, and for accurately describing study samples, all critical elements for reducing tobacco-related disparities, and improving diversity, equity, and inclusion in TUD treatment research.